Peran Organisasi Otonom Muhammadiyah dalam Pemberdayaan Perempuan di Kota Tangerang - Rizky Septiyansah; Muhammdah Riyan; Milana Abdillah; Indra Maulana; Ahmad Rokhsan Cholis (Student Research Journal, 2024)
Women's empowerment is an important component in sustainable development and social welfare. Muhammadiyah, as one of the largest Islamic organizations in Indonesia, has played a significant role in efforts to empower women through its autonomous organizations, namely 'Aisyiyah and Nasyiatul 'Aisyiyah. This article aims to examine the role of these organizations in improving the quality of life of women in Indonesia. This research uses a qualitative descriptive method with secondary data analysis from various relevant sources. 'Aisyiyah, founded in 1917, focuses on empowering women through education, health and activities socio-economic. Various programs have been implemented, including establishment educational institutions, health clinics, and skills training programs. Nasyiatul 'Aisyiyah, founded in 1931, targets young women with programs that include education, skills training, and women's rights advocacy